1972
DOI: 10.1103/physrevlett.29.137
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Range Gravity: A Generally Covariant Model

Abstract: A generally covariant classical model for gravity, which in the limit of weak fields is essentially equivalent to Fujii's massive dilaton theory, is obtained when the invariance under a group of space-time-dependent geometry-preserving mass-unit transformations of a scalar-tensor theory is broken by ascribing a mass to the scalar field. The experimental consequences are discussed.In recent articles 1 * 2 Fujii has proposed a theory in which a nonzero mass is ascribed to the Nambu-Goldstone boson of scale invar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
221
0
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(226 citation statements)
references
References 4 publications
4
221
0
1
Order By: Relevance
“…The third equation (16) is the "Klein-Gordon" (-like) equation for the field φ which with the use of (15) gives the fourth-order equation. However while the fourth-order f (R)-gravity is equivalent with a Brans-Dicke scalar field, and specifically with the O'Hanlon theory [50], that is not true for our model where indeed the higher-order derivatives are describing by the field φ, but it is not a canonical field. On the other hand the field equations are more close to that of a particle in the Generalized Uncertainty principle [13], where as the position of the particle now we consider that of the scale factor a(t).…”
Section: Field Equations In F (T B) = T + F (B)mentioning
confidence: 91%
See 1 more Smart Citation
“…The third equation (16) is the "Klein-Gordon" (-like) equation for the field φ which with the use of (15) gives the fourth-order equation. However while the fourth-order f (R)-gravity is equivalent with a Brans-Dicke scalar field, and specifically with the O'Hanlon theory [50], that is not true for our model where indeed the higher-order derivatives are describing by the field φ, but it is not a canonical field. On the other hand the field equations are more close to that of a particle in the Generalized Uncertainty principle [13], where as the position of the particle now we consider that of the scale factor a(t).…”
Section: Field Equations In F (T B) = T + F (B)mentioning
confidence: 91%
“…, we see that f ,T = −f ,B = −φ, which means that the Lagrangian of O'Hanlon gravity 2 [50] is recovered.…”
Section: Lagrange Multiplier and Minisuperspacementioning
confidence: 95%
“…The Lagrangian of f (R) theories corresponds to L = (M 2 pl /2) f (R), where f is an arbitrary function in terms of the Ricci scalar R. This is equivalent to the Lagrangian (1) by choosing the following functions [51] …”
Section: A F (R) Theoriesmentioning
confidence: 99%
“…gravity is equivalent to a scalar-tensor theory [23,24]. One varies the action to calculate the equations of motion,…”
Section: Gravitational Wave Polarizations In F (R) Gravitymentioning
confidence: 99%
“…Our analysis showed that the extra polarization state is the transverse breathing mode if the scalar field is massless, and it is a mix of the transverse breathing and the longitudinal modes if the scalar field is massive [21]. f (R) gravity [22] is equivalent to a scalar-tensor theory of gravity [23,24]. The equivalent scalar field is massive, and it excites both the longitudinal and transverse breathing modes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%